Effect of pH on Domestic Wastewater Treatment Efficiency with Biofilter Media Plastic Mineral Water Bottle Cap - Wardani, Yasminda Ika; A, Syarifudin; Hamzani, Sulaiman; Ali As, Zulfikar (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2023)
Domestic wastewater can be defined as water that comes from human activities and contains various types of harmful pollutants, such as TSS. Direct discharge of these pollutants into water-receiving bodies can cause pollution of aquatic ecosystems. Therefore, it must be treated to meet the appropriate air quality standards before being discharged to the air-receiving body. This study aims to determine the effect of pH on the efficiency of domestic wastewater treatment using mineral water plastic bottle caps with an anaerobic biofilter method. The study was conducted using an experimental method in two anaerobic biofilter reactors, with variations in the number of treatments of 100 and 300 bottles of bottle cap media and contact times for 0 days and 4 days, respectively. Anaerobic biofilter research results show that pH influences the efficiency of domestic wastewater treatment with mineral water plastic bottle caps in accordance with quality standards. The optimum pollutant removal value was found at a contact time of 4 days, which was 46% on 300 pieces of media. The use of a biofilter with a plastic bottle cap media can be an alternative to treating organic wastewater that has a low load, such as household wastewater. Further research can be done by adding more pores in the bottle cap media to improve the performance of the biofilter, as well as increasing the contact time variation treatment and the amount of bottle cap media used.